Boosting Indonesia’s creative industries: Identification of people’s characteristics and creative behaviour - Setiadi, Nugroho J.; Wahdiaman (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2012)
The purpose of this paper is to suggest an empirical model to assess personal characteristics and creative behaviour among creative workers in Indonesia’s creative industries. It is critical for people to do their best to ensure and realise that creativity is one of the most important elements in order to achieve high performance. Although a few previous studies have focused on the understanding of how the myriad of interacting potential creators can foster their performance, the characteristics and behaviour patterns of Indonesia’s creative workers are not well identified yet. Considering this, a new measure has been developed and evaluated with a group of creative workers (N = 220). This study presents data supporting the reliability (internal consistency) and validity (criterion and construction) of this multidimensional instrument. The results of factor analysis indicated a fivefactor solution. These factors demonstrated adequate internal consistency and correlations with the established measures of the Big-Five personality (e.g. the NEO-FFI of Costa & McCrae 1992). It was found that the most important elements determining the characteristics of creative people are enthusiasm, a low depression level, self-discipline, trust, and ideas.
Keywords: creativity; creative workers; personal characteristics; creative behaviour; creative industry